1998
DOI: 10.1002/(sici)1098-2396(199810)30:2<119::aid-syn1>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy for the treatment of cocaine addiction

Abstract: Cocaine's addictive liability has been linked to its pharmacologic actions on mesotelencephalic dopamine (DA) reinforcement/reward pathways in the central nervous system (CNS). Dopaminergic transmission within these pathways is modulated by gamma-aminobutyric acid (GABA). With this knowledge, we examined the utility of gamma vinylGABA (GVG), a selective and irreversible inhibitor of GABA-transaminase (GABA-T) known to potentiate GABAergic inhibition, to alter cocaine's biochemical effects as well as its effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
136
1
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 183 publications
(153 citation statements)
references
References 46 publications
(41 reference statements)
14
136
1
2
Order By: Relevance
“…Further, we demonstrated that GVG blocked cocaine self-administration and cocaineinduced lowering of brain stimulation reward thresholds (Kushner et al, 1997). In addition, we demonstrated that GVG blocked the expression and acquisition of cocaine-seeking behavior (conditioned place preference, Dewey et al, 1998) as well as sensitization to cocaine (Gardner et al, 2002). We subsequently extended this work to include similar findings with heroin, nicotine, methamphetamine and amphetamine, and alcohol Paul et al, 2001a;Dewey et al, 1999).…”
supporting
confidence: 53%
“…Further, we demonstrated that GVG blocked cocaine self-administration and cocaineinduced lowering of brain stimulation reward thresholds (Kushner et al, 1997). In addition, we demonstrated that GVG blocked the expression and acquisition of cocaine-seeking behavior (conditioned place preference, Dewey et al, 1998) as well as sensitization to cocaine (Gardner et al, 2002). We subsequently extended this work to include similar findings with heroin, nicotine, methamphetamine and amphetamine, and alcohol Paul et al, 2001a;Dewey et al, 1999).…”
supporting
confidence: 53%
“…Also, GABA B receptor agonists inhibit both cocaine self-administration (Roberts et al, 1996;Roberts, 2005) and cocaine-triggered reinstatement of drug-seeking behavior (Campbell et al, 1999;Di Ciano and Everitt, 2003). Second, elevation of extracellular GABA levels by inhibition of GABA degradation by γ-vinyl GABA (GVG) inhibits the rewarding effects of cocaine as assessed by intravenous self-administration, conditioned place preference and electrical brain stimulation reward (Kushner, 1997;Kushner et al, 1999;Dewey et al, 1998). GVG has also been reported to inhibit cocaine-enhanced NAc DA levels (Dewey et al, 1998;Schiffer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Second, elevation of extracellular GABA levels by inhibition of GABA degradation by γ-vinyl GABA (GVG) inhibits the rewarding effects of cocaine as assessed by intravenous self-administration, conditioned place preference and electrical brain stimulation reward (Kushner, 1997;Kushner et al, 1999;Dewey et al, 1998). GVG has also been reported to inhibit cocaine-enhanced NAc DA levels (Dewey et al, 1998;Schiffer et al, 2003). Furthermore, clinical trials with the GABA A receptor modulator topiramate, the GABA B receptor agonist baclofen, or the GABA enhancers GVG or tiagabine (a GABA-uptake inhibitor) have shown significant decreases in self-reported cocaine craving and urine-confirmed cocaine use (Kampman et al, 2004;Shoptaw et al, 2003;Johnson, 2005;Brodie et al, 2003;González et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, several other neurotransmitter/neuromodulator systems functionally linked to DA neurons within the motivational circuit may also contribute to the complex regulations underlying cocaine dependence (Dewey et al, 1998;de Vries et al, 2001;Sarnyai et al, 2001;Kreek et al, 2002;Beinfeld, 2003;Baptista et al, 2004). Therefore, new approaches investigating the potential of modulatory systems as alternative targets may be of fundamental importance.…”
Section: Introductionmentioning
confidence: 99%